Biostratigraphy and paleoenvironment correlation based on benthic foraminifera from the cenozoic Marajó and Pirabas formations, Eastern Amazon Coast, Brazil. (December 2022) - Garzón Rojas, Laura Estefanía; Nogueira, Anna Andressa Evangelista; Soares, Joelson Lima; Rodrigues Nogueira, Afonso Cesar; Júnior, Manoel Imbiriba
Abstract: The Oligocene-Miocene foraminifera biostratigraphy correlation has been applied successfully as a geological tool for establishing the paleoenvironmental conditions during the deposition of siliciclastic and carbonate strata in the Eastern Amazon coastal basins. In this region, previously interpreted tectonic compartments represented by the Marajó Basin and Bragantina Platform were the main sites of siliciclastic and carbonate sedimentation influenced by Late Paleogene-Neogene transgressive–regressive events. In the subsident Marajó basin, a siliciclastic estuary was developed, supplied by the Cratonic Amazon River. The transcontinental river did not influence the Bragantina region to the East, allowing the implantation of a shallow carbonate platform. These Neogene segments require further sedimentological, stratigraphic, and paleontological studies to define these limits. The use of foraminifera content has been considered an important tool to assist in this differentiation, providing a paleoenvironmental and paleoecological reconstruction model. This work used qualitative and quantitative analyses integrating several diversity indices, complementing the R-mode cluster and the correlation of planktonic and benthic (P/B) ratios. The similarity in faunal diversity indicated that these siliciclastic and carbonate units represented by the Marajó and Pirabas formations are chronocorrelated. Marajó Formation is interpreted as a restricted, suboxic, marginal marine environment (lagoons/mangroves) with variable salinity and abundance of the species as Cribroelphidium williamsoni, Ammonia tepida, and A. beccari. In contrast, the Pirabas Formation was deposited in a brackish, oxic, and carbonate platform characterized by Cibicidoides subhaidingerii, Cibicides pachyderma A. beccarii, and Cassidulina laevigata species. These foraminifera assemblages confirm the previous stratigraphic and paleoenvironmental interpretations providing new insights into understanding the Late Paleogene-Neogene evolution of the Eastern Amazonia Coast. Highlights: Biostratigraphy correlation as a geological tool for establishing the paleoenvironmental conditions. Restricted marginal marine environment (estuaries/mangroves). Inner, middle to outer neritic platform marginal marine environment. Similarity in faunal diversity and behave as chronocorrelates, delimiting the Oligo-Miocene age. Late Paleogene-Neogene evolution of the Eastern Amazonia Coast.